Assignment Tokyo : - Meyer, Armin H. (Bobbs-Merrill, 1974)
The postwar development of Japan has been nothing less than phenomenal. Within a quarter of a century, a nation which was physically devastated and morally crushed rose to become one of the world's three leading industrial powers.